2021
DOI: 10.1002/ange.202100064
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Engineered Polypeptide Adhesive Coacervates for Surgical Applications

Abstract: Adhesive hydrogels have been developed for wound healing applications.H owever,t heir adhesive performance is impaired dramatically due to their high swelling on wet tissues. To tackle this challenge,w ef abricated an ew type of nonswelling protein adhesive for underwater and in vivo applications.I nt his soft material, the electrostatic complexation between supercharged polypeptides with oppositely charged surfactants containing 3,4-dihydroxylphenylalanine or azobenzenemoieties playsanimportant role for the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…In contrast, the lap‐shear strength decreased significantly when the charge ratio was further increased to 1:1.3. In combination with our previous studies, [ 22,30 ] the presence of excess positive charge in the coacervate favors the formation of cation–π interaction, which significantly influences the adhesion performance. These lap shear tests further confirmed that cation–π interactions are crucial for strong interfacial adhesion.…”
Section: Resultssupporting
confidence: 75%
“…In contrast, the lap‐shear strength decreased significantly when the charge ratio was further increased to 1:1.3. In combination with our previous studies, [ 22,30 ] the presence of excess positive charge in the coacervate favors the formation of cation–π interaction, which significantly influences the adhesion performance. These lap shear tests further confirmed that cation–π interactions are crucial for strong interfacial adhesion.…”
Section: Resultssupporting
confidence: 75%
“…The viscous hydrogels usually swell when used for tissue adhesion, resulting in a sharp drop in its mechanical properties, which in turn causes the rupture of the viscous hydrogel during the wound healing process. In order to meet this challenge, Liu et al 86 have creatively developed a non‐swelling protein adhesive with strong adhesive properties. The material relied on electrostatic complexation between supercharged polypeptides and bionic synthetic surfactants (containing 3, 4‐dihydroxyphenylalanine or azophenyl groups) with opposite charges to form a super‐viscous cohesive layer.…”
Section: Nature‐inspired Adhesivesmentioning
confidence: 99%
“…Marine sessile organisms are impressive for their miraculous ability to secrete adhesive proteins, which can stably position themselves on diverse substrates in seawater. Drawing inspiration from these natural systems, numerous efforts have been invested to create biomimetic adhesives aiming at hemostasis, wound dressing, bone fixing, drug delivery, and antimicrobial application. Most of the reported examples are the covalent polymer or recombinant protein adhesives. Only recently, the peptide-based underwater adhesives have started to garner increasing attention because of their incredible advantages in the functional recapitulation of adhesive proteins and the construction of adhesive biomaterials. , Comparing with the recombinant proteins, peptides with short chains are favorable for practical applications because of their relative ease of synthesis and purification, lending themselves ready to be scaled up. In addition, the constituents and structures of peptides are similar to those of proteins, which provide a simple model to scrutinize the adhesion mechanism of natural proteins. , Comparing with the synthetic polymers, peptides have great potential in the development of biomaterials due to their inherent biocompatibility and biodegradability. , In earlier reports, the studies on peptide adhesion were mainly limited to the interfacial attachment and adhesion, ,,, while the poor bulk cohesion of short peptides was a long neglected issue.…”
Section: Introductionmentioning
confidence: 99%